Physical exercise in advanced cancer patients undergoing palliative treatment. Issue 6 (1st November 2016) - Titz, Christina; Hummler, Simone; Thomas, Michael; Wiskemann, Joachim
ABSTRACT: Introduction : Physical exercise intervention programs show beneficial effects in early stage cancer patients during and after treatment. There is also growing evidence that physical exercise is safe and feasible for advanced cancer patients but knowledge is limited. Areas covered : This review provides an overview of randomized controlled exercise trials implemented in palliative care settings with advanced cancer patients. A comprehensive literature search was carried out in PubMed (MEDLINE), CINAHL, and the Cochrane Library. Six articles providing data of 590 patients met the predefined inclusion criteria. Mainly resistance exercise was applied and duration of interventions was between 8 and 16 weeks. Expert commentary : Beneficial effects for exercise patients were reported for both physical and psychological outcomes. However, general exercise recommendation for patients undergoing palliative treatment cannot be derived from the six analyzed studies. This is due to large heterogeneity of the applied exercise programs, included patient groups and performed assessment methods.